Special Autonomy of Yogyakarta in the Context of Local Autonomy Law - Sidiq, Muhamad Abdulah (Law Research Review Quarterly, 2021)
Local government is the authority of the autonomous regions to organize and manage the interests of local people according to their own initiative based on community aspirations in accordance with the laws and regulations. In response to the demands of government reform quite quickly, it has undertaken a sufficiently fundamental breakthrough of the various laws in the political field from the centralist-autoritarian to the autonomous-democratic. After successfully compiling the three laws on the political field that became the basis of the election in 1999 the government immediately followed him with a new law in the field of special politics on power relations between the central and local, namely Law no. 22 of 1999 on Regional Government and Law No. 25 of 1999 on Financial Relations between Central and Regional. The formation of regions is basically intended to improve public services in order to accelerate the realization of community welfare as well as political education at the local level. Considerations and other conditions that enable the area to organize and realize the purpose of the establishment of the region and the granting of regional autonomy. The Government may designate special areas in the autonomous regions to carry out specific government functions that are specific to national and / or national-scale interests "special" for the interests and benefit of Indonesia. One of these special autonomous regions is the Special Region of Yogyakarta that has been recognized special autonomous region in Law No.13 of 2012 on the privilege of Yogyakarta.